Pengembangan Lembar Kerja Peserta Didik Berbasis Realistic Mathematics Education Menggunakan Konteks Wisata “Muratara” untuk Meningkatkan Kemampuan Literasi Matematika Siswa Kelas IV - Reza Fahlevi; Agus Susanta; Irwan Koto (UNIB Press, 2024)
This study aims to analyze the development of student worksheets based on Realistic Mathematics Education on approximations that are valid, feasible, effective, and improve the Mathematical literacy skills of grade IV students. This research is research and development (R&D) using the ADDIE model. The subjects in the study was grade IV students at SD Negeri 6 Muara Rupit. The research instrument used validation sheets, student response questionnaire sheets and question test sheets. Data from the development of student worksheets were then analyzed using Gregory calculations and interrater reliability, student responses were analyzed using the Guttman scale with the checklist method as well as quantitative analysis using the t-test. From this study it is known that language validation, material and presentation of student worksheets are very suitable for use in learning, so that students are happy and interested in following the lesson. Based on the N-Gains test using LKPD, 37.5% of students got an N-gain score with high criteria, and 62.5% got an N-gain score with medium criteria. So that the Mathematical literacy skills of students who use RME-based worksheets using the